Experimental Generation of Quasi-Zero-Order Mathieu-Gauss Beams via Diffractive Elements in THz Domain - Haifeng Shi; Kejia Wang; Zhengang Yang; Jinsong Liu (IEEE Photonics Journal, 2021)
We first demonstrate the Terahertz quasi-zero-order Mathieu-Gauss beams with a 0.1-THz continuous wave. To generate these beams, two diffractive elements, a cylindrical lens and an axicon bearing specific phases are fabricated via 3D printing technology. The related numerical simulations are conducted to study intensity distributions and properties on non-diffraction and self-healing of THz quasi-zero-order Mathieu-Gauss beams in free space. Experimental results are in good agreement with numerical ones. Based on the characteristic of terahertz Mathieu-Gauss beams, they can be applied to terahertz linear array imaging system and terahertz communication.